Using speech-to-text technology to empower young writers with special educational needs. (April 2023) - Kambouri, Maria; Simon, Helen; Brooks, Greg
Abstract: This article reports the first group-based intervention study in the UK of using speech to-text (STT) technology to improve the writing of children with special educational needs and disabilities (SEND). Over a period of five years, thirty children took part in total from three settings; a mainstream school, a special school and a special unit of a different mainstream school. All children had Education, Health and Care Plans because of their difficulties in spoken and written communication. Children were trained to use the Dragon STT system, and used it on set tasks for 16–18 weeks. Handwritten text and self-esteem were assessed before and after the intervention, and screen-written text at the end. The results showed that this approach had boosted the quantity and quality of handwritten text, with post-test screen-written text significantly better than handwritten at post-test. The self-esteem instrument also showed positive and statistically significant results. The findings support the feasibility of using STT to support children with writing difficulties. All the data were gathered before the Covid-19 pandemic; the implications of this, and of the innovative research design, are discussed. Highlights: This is the first UK study on using speech-to-text (STT) systems to improve the writing of children with SEND. Thirty children with communication difficulties participated, They and teachers were trained on the Dragon STT system, and used it for 16–18 weeks. Their self-esteem (statistically significant increase) and hand-written text were assessed before and after the intervention, and screen-written text at the end. The intervention boosted the quantity and quality of handwritten text, with screen-written text significantly better than handwritten text at post-test. The findings show effective use of STT systems to support children with SEND who have writing difficulties.